2011
DOI: 10.1002/jbmr.401
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 23 regulates renal 1,25-dihydroxyvitamin D and phosphate metabolism via the MAP kinase signaling pathway in Hyp mice

Abstract: In X-linked hypophosphatemia (XLH) and in its murine homologue, the Hyp mouse, increased circulating concentrations of fibroblast growth factor 23 (FGF-23) are critical to the pathogenesis of disordered metabolism of phosphate (Pi) and 1,25-dihydroxyvitamin D [1,25(OH)2D]. In this study, we hypothesized that in Hyp mice, FGF-23-mediated suppression of renal 1,25(OH)2D production and Pi reabsorption depends on activation of mitogen-activated protein kinase (MAPK) signaling. Wild-type and Hyp mice were administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 47 publications
5
54
1
Order By: Relevance
“…FGF receptor can activate several signal transduction pathways including phosphorylation of mitogen-activated protein kinase (MAPK), phosphoinositide 3-kinase, and phospholipase Cc [42]. The inhibitor of MAPK, PD0325901, was shown to increase serum phosphate and 1,25(OH) 2 D levels in Hyp mice [6]. Long-term treatment with the inhibitor enhanced mineralization and increased bone mineral density of Hyp mice [9].…”
Section: Fgf23-fgf Receptor/klotho Pathway As a Drugmentioning
confidence: 97%
See 1 more Smart Citation
“…FGF receptor can activate several signal transduction pathways including phosphorylation of mitogen-activated protein kinase (MAPK), phosphoinositide 3-kinase, and phospholipase Cc [42]. The inhibitor of MAPK, PD0325901, was shown to increase serum phosphate and 1,25(OH) 2 D levels in Hyp mice [6]. Long-term treatment with the inhibitor enhanced mineralization and increased bone mineral density of Hyp mice [9].…”
Section: Fgf23-fgf Receptor/klotho Pathway As a Drugmentioning
confidence: 97%
“…These findings suggest that FGF23-FGF receptor/Klotho pathway can be a new drug target for disorders of mineral and bone metabolism. Actually, several preclinical studies indicated that the inhibition of FGF23 activities may be useful for hypophosphatemic diseases caused by excessive actions of FG23 [3][4][5][6][7][8][9]. In addition, the results of phase I-II clinical trials of neutralizing anti-FGF23 antibody were published [10,11].…”
Section: Introductionmentioning
confidence: 97%
“…In Hyp mice, a mouse model of the human disease XLH which is characterized by increased endogenous Fgf23 secretion, it was shown that the elevated serum Fgf23 levels are correlated with increased ERK1/2 signaling, and that blockade of ERK1/2 in the kidney of Hyp mice improves hypophosphatemia, 1,25(OH) 2 D deficiency, and the skeletal mineralization defects [56,57]. The transcription factor egr-1 is a downstream target of FGF23-induced ERK1/2 activation [14].…”
Section: Proximal Tubular Vitamin D Hormone Synthesismentioning
confidence: 99%
“…2). 18,149,217 These signals lead to phosphorylation of the Na þ /H þ exchange regulatory cofactor (NHERF) 1, which causes existing cotransporters to be removed from the brush-border membrane of renal tubular epithelial cells, and reduced expression of renal tubular Na/P II cotransporters. 6,139 In addition, the ERK-1/2 pathway (induced by FGF23) downregulates renal 1a-hydroxylase expression.…”
Section: Klothomentioning
confidence: 99%